Charles Hutton and the ‘Dissensions’ of 1783–84: Scientific networking and its failures - Wardhaugh, B (Royal Society, 2016)
This paper proposes a fresh look at the ‘Dissensions’ that held up scientific business at the Royal Society during the spring of 1784. It focuses attention on the career and personal networks of Charles Hutton, whose dismissal from the role of Foreign Secretary ignited the row. It shows that the incident had no single cause but was the outcome of a number of factors that made Hutton intolerable to Joseph Banks, president of the Society, and of a number of factors that made Banks unpopular as President among a group of about forty otherwise rather disparate fellows.